The Role of Employees' Personality Characteristics in Job Performance and Satisfaction during Digitization Years - Giannoukou, Ioanna (Technium Business and Management, 2023)
This paper summarizes the association between employees' personality traits and their job performance and satisfaction levels. Comprehending this correlation is crucial for organizations aiming to maximize employee well-being and productivity. The impact of personality traits on workplace dynamics has been widely acknowledged for a considerable period. Extensive research has been conducted on the Five-Factor Model (FFM) of personality, which comprises conscientiousness, extraversion, agreeableness, openness to experience, and emotional stability (neuroticism) concerning job performance and satisfaction. The primary objective of this systematic review was to examine the correlation between personality traits and job performance and satisfaction. Most existing literature predominantly revolves around the Big Five personality theory, which encompasses five key dimensions: agreeableness, extraversion, neuroticism, conscientiousness, and openness to experience. A total of twenty-two articles were subjected to analysis, out of which fifteen articles met the inclusion criteria. These criteria encompassed the requirement for articles to be written in English, to be directly relevant to the topic under investigation, to utilize workers as the study sample, and to have been published in reputable scientific journals. The findings indicated a robust correlation between personality traits and job performance and job satisfaction, with the former exerting a substantial influence on work outcomes. More specifically, according to the Big 5 factor model, neuroticism has been found to impact job performance and satisfaction significantly negatively. Conversely, it is noteworthy that traits such as extroversion and conscientiousness exclusively positively influence work-related factors. In summary, employees' personality traits have a notable impact on their job performance and level of satisfaction. Organizations can derive advantages by acknowledging these dynamics when engaging in recruitment, role design, and provision of developmental opportunities. The significance of personality should be taken into account in conjunction with other contextual and individual factors in order to achieve a comprehensive comprehension of employee well-being and performance.